OP0194 The association between serum uric acid and arterial stiffness in a low-risk, large population of middle-aged korean. (12th June 2018) - Hwang, J.; Hwang, J.H.; Eun, Y.; Kim, H.; Lee, J.; Ahn, J.K.
Abstract : Background: Arterial stiffness occurs because of biologic ageing and arteriosclerosis, and is most commonly measured by pulse-wave velocity. Several studies have reported that high serum uric acid may contribute to the development of a number of metabolic and haemodynamic abnormalities, and multivariate analyses in epidemiologic studies have suggested that hyperuricemia is an independent risk factor for arterial stiffness in those with comorbidities such as diabetes, hypertension, and chronic kidney disease. However, there are few reports about the association between SUA and arterial stiffness in apparently healthy populations. Objectives: We aimed to investigate the association between serum uric acid (SUA) and arterial stiffness as evaluated by brachial ankle pulse wave velocity (baPWV) in a low-risk, large, middle-aged Korean population. Methods: We conducted a cross-sectional study of 66, 917 Koreans (38 170 men, 28 747 women) who received yearly screening with available PWV and SUA results. None of the participants had coronary heart disease, diabetes, or hypertension. SUA was divided into quintiles for assessment of its association with baPWV by multiple linear regression analysis. Results: The average SUA level was 5.23±1.4 mg/dl, and SUA values were higher in men than in women (6.1±1.2 mg/dl vs 4.1±0.8 mg/dl). In multiple regression analysis, PWV was significantly higher in SUA quintiles 2–5 compared to the lowest group (reference) (coefficient=11.52, 18.19, 24.73, and 31.02 cm/s, respectively). In female subjects, the average difference (cm/s) of PWV between quintiles 2–5 and quintile 1 of SUA was 13.1, 22.9, 34.6, and 32.1, respectively. Fully adjusted linear coefficient β (S.E.) was 6.62 (0.70) and 12.43 (1.33) in all participants and female subjects, respectively (p<0.001). In contrast, there was a J-shaped association between PWV and SUA quintile among males. When modelled continuously, each 1 mg/dl higher SUA level was associated with 0.27 higher baPWV (p<0.001) in the adjusted analysis. Conclusions: These findings indicate that higher SUA levels could have an unfavourable impact on arterial stiffness as measured by baPWV in a low-risk, large, middle-aged Korean population. Disclosure of Interest: None declared